Structural dynamics in the water and proton channels of photosystem II during the S2 to S3 transition - Rana Hussein (Nature Portfolio, 2021)
The oxygen-evolving complex in Photosystem II (PSII) catalyzes the light-driven oxidation of water to oxygen and it is still under debate how the water reaches the active site. Here, the authors analyse time-resolved XFEL-based crystal structures of PSII that were determined at room temperature and report the structures of the waters in the putative channels surrounding the active site at various time-points during the reaction cycle and conclude that the O1 channel is the likely water intake pathway and the Cl1 channel the likely proton release pathway.